The impact of climate change and policies on productivity: A report of the ESCB Expert Group on productivity, innovation and technological changes - Sofia Anyfantaki; Andrea Colciago; Jan De Mulder; Elisabeth Falck; Vincent Labhard; Paloma López-García; Nuno Lourenço; Jaanika Meriküll; Miles Parker; Oke Röhe; Joachim Schroth; Patrick Schulte; et al. (European Central Bank (ECB), 2024)
The impact of climate change on European Union (EU) countries and regions is poised to exhibit considerable diversity, influenced by factors encompassing average temperature, sectoral composition, developmental stages, and adaptation endeavours. The transition towards a more climate-friendly economy demands a well-orchestrated approach to mitigate enduring productivity costs. This shift will have varied implications for businesses, contingent upon their scale, access to financial resources, and capacity for innovation. The formulation of transition policies holds the potential to foster green innovation without displacing other initiatives, yet stringent climate regulations might impede the productivity ascent of pollutantemitting enterprises. It will thus take time to reap the benefits of innovation. The efficacy of the policy mix is of critical importance in determining the trajectory of success. Market-driven mechanisms exhibit milder distortions compared to nonmarket-based strategies, though they may not inherently stimulate innovation. Significantly, subsidies earmarked for green research and development (R&D) emerge as a pivotal instrument for fostering innovation, thus constituting a vital component of the policy repertoire during the green transition. The implementation of transition policies will inevitably trigger a substantial reallocation of resources among and within sectors, potentially carrying short-term adverse ramifications. Notably, considerable productivity disparities exist between top and bottom emitters within specific industries. The transition period poses a risk to a substantial proportion of firms and can erode employment opportunities, with a likely decline in new ventures within affected sectors.
Keywords: D24; L52; O33; O38; Q54; Q58; 330; climate change impact; productivity; transition risk; climate transitionpolicies; physical risk; green innovation; economic reallocation